Magmatic and metamorphic evolution of the Stolzburg Block, Barberton Granitoid-Greenstone Terrain - Muhlberg, Moritz (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.